IMPLEMENTATION OF THE GREEN DEAL POLICY IN UKRAINIAN LEGISLATION: THEORETICAL AND PRACTICAL CHALLENGES - Trotsiuk, Nina; Kononenko, Anna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of this research is to conduct a comprehensive examination of Ukraine’s process of Eurointegration into the European Union by analyzing the amendments needed in national legislation for the adoption and adaptation of the Green Deal policy and its provisions to the Ukrainian context. This objective encompasses several tasks: analyzing the current state of national legislation and its alignment with EU legislation; exploring the theoretical foundations and practical experiences of the EU in implementing and developing the key aspects of the Green Deal policy; examining the legal content of the main principles of the Green Deal policy and their practical application; identifying current issues in state regulation and national legislation related to the implementation of the Green Deal policy; and outlining prospects for improving legislation regarding the implementation of Green Deal principles in the context of Eurointegration. Research methods: the primary results of the study were obtained using the dialectical method, which allowed for an exploration of the specifics of the level of harmonization of Ukrainian legislation. The normative method was employed to analyze Ukrainian legislation; the systemic and theoretical methods facilitated the analysis of the objectives and effectiveness of Green Deal implementation in the context of Eurointegration. The concrete-sociological method was used to illustrate theoretical conclusions and positions of the research. The study results include a thorough assessment of the alignment of Ukrainian legislation with European Green Deal standards, identification of key issues and gaps in the implementation of environmental policy, and the development of specific recommendations for improving legal and practical mechanisms. The research also aims to identify barriers to implementation, such as financial and administrative obstacles, and propose strategic approaches for the effective integration of the Green Deal policy into Ukraine’s national sustainable development strategies. The discussion focuses on critical aspects of adapting European environmental standards to Ukrainian realities. It includes a detailed analysis of how theoretical Green Deal models translate into practical initiatives and policies in Ukraine, considering the specifics of national legislation, economic, and social conditions. Particular attention is given to discrepancies and issues in the legal framework, as well as the effectiveness of existing tools and mechanisms. The discussion also covers prospects for further legislative and practical improvements that will facilitate the successful implementation of the Green Deal in Ukraine, as well as potential scenarios for overcoming existing barriers and achieving environmental goals.